Islam Minoritas di Laos (Prosiding Keislaman dan Sains, 2025)
Muslims are a minority in Laos, a communist country in Southeast Asia. Despite their small numbers, Muslims in Laos have managed to adapt and thrive in the country, maintaining their religious identity and engaging in various economic activities. This article highlights the challenges they face, such as limited access to Islamic education and funding for mosque construction, but also emphasizes their resilience and the tolerance of Lao society. The history of Islam's entry into Laos, which was initiated by Chinese traders from Yunnan who brought the religion to the country. The article also details the various groups that make up the Muslim population, including Champa Muslim refugees from Cambodia and South Asian immigrants. These diverse groups have formed a cohesive community, maintaining their distinct cultural and religious practices while coexisting peacefully with Laos' predominantly Buddhist population. Despite facing challenges, Muslims in Laos are generally well integrated and enjoy religious freedom. This is in contrast to the situation of Muslim minorities in other parts of Indochina, such as Cambodia, where they face greater persecution. This article suggests that the Lao government's commitment to religious freedom, combined with the resilience of the Muslim community, has enabled them to thrive in a context that could have been much more challenging.